Od predmetov do simbolov - Schippers, Thomas K. (Etnolog. Nova vrsta (Ljubljana), 2002)
The central topic of this paper concerns the study of the material aspects of culture within European ethnology or Volkskunde. This disciplinary sub-field, has undergone quite spectacular changes during the last half century. In this paper the author would like to point out some milestones of how European ethnology has approached and analysed the material dimensions of human cultures.
Keywords: ethnology; etnologija; materialna kultura; muzeologija; teorija; theory; Europe; Evropa